Bridging traditions : alchemy, chemistry, and Paracelsian practices in the early modern era - Parshall, Karen Hunger, 1955-; Walton, Michael Thomson, 1945-; Moran, Bruce T. (Early modern studies series., 2015)
Bridging Traditions explores the connections between apparently different zones of comprehension and experience--magic and experiment, alchemy and mechanics, practical mathematics and geometrical mysticism, things earthy and heavenly, and especially science and medicine--by focusing on points of intersection among alchemy, chemistry, and Paracelsian medical philosophy. In exploring the varieties of natural knowledge in the early modern era, the authors pay tribute to the work of Allen Debus, whose own endeavors cleared the way for scholars to examine subjects that were once snubbed as suitable only to the refuse heap of the history of science.